Magnetoresistance effect in (La, Sr)MnO3 bicrystalline films - Alejandro, G.; Steren, L. B.; Pastoriza, H.; Vega, D.; Granada, M.; Rojas Sánchez, J. C.; Sirena, M.; Alascio, B. (IOP Publishing, 2010)
Fil: Alejandro, G. Comisión Nacional de Energía Atómica; Argentina